Template synthesis of polyaniline in presence of polymeric sulfoacid - M. A. Guseva; O. L. Gribkova; A. A. Isakova; V. F. Ivanov; Yu. A. Fedotov; V. A. Tverskoy (Тонкие химические технологии)
It was investigated the influence of the correlation of sulfoacid and aniline concentration on the polymerization of the latter when it was protonated by polymeric sulfoacid and on electronic structure of forming polyaniline.